2014
DOI: 10.1371/journal.pone.0088684
|View full text |Cite
|
Sign up to set email alerts
|

Improved Glucose Metabolism In Vitro and In Vivo by an Allosteric Monoclonal Antibody That Increases Insulin Receptor Binding Affinity

Abstract: Previously we reported studies of XMetA, an agonist antibody to the insulin receptor (INSR). We have now utilized phage display to identify XMetS, a novel monoclonal antibody to the INSR. Biophysical studies demonstrated that XMetS bound to the human and mouse INSR with picomolar affinity. Unlike monoclonal antibody XMetA, XMetS alone had little or no agonist effect on the INSR. However, XMetS was a strong positive allosteric modulator of the INSR that increased the binding affinity for insulin nearly 20-fold.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Initial pilot studies have demonstrated the feasibility of this approach (66,67). Finally, antibody-mediated blockade of the insulin receptor, decreasing insulin signaling, can prevent hypoglycemia in mice (68) and may modify glucose patterns in pilot human studies (69). Until further clinical studies are performed, the role of these potential therapies remains uncertain.…”
Section: Experimental Approachesmentioning
confidence: 99%
“…Initial pilot studies have demonstrated the feasibility of this approach (66,67). Finally, antibody-mediated blockade of the insulin receptor, decreasing insulin signaling, can prevent hypoglycemia in mice (68) and may modify glucose patterns in pilot human studies (69). Until further clinical studies are performed, the role of these potential therapies remains uncertain.…”
Section: Experimental Approachesmentioning
confidence: 99%
“…Neither one of the RTK binding domains recognized by these antibodies constitute the orthosteric site, so the clinical effects of both agents are likely allosteric. Other allosteric RTK antibodies have been discovered, such as XMetA and XMetS, which bind to the ECD of the insulin RTK and activate the receptor or act as an insulin‐sensitizing PAM . Allosteric ECD interactions have also been identified at RTKs mediated by peptidomimetics .…”
Section: Allosteric Modulatory Sites and Their Pharmacologymentioning
confidence: 99%
“…Other allosteric RTK antibodies have been discovered, such as XMetA and XMetS, which bind to the ECD of the insulin RTK and activate the receptor or act as an insulin-sensitizing PAM. 192,193 Allosteric ECD interactions have also been identified at RTKs mediated by peptidomimetics. 189 Most recently, the first ECD small-molecule RTK inhibitor was identified ( Figure 5).…”
Section: Allosteric Sites On Rtksmentioning
confidence: 99%